Quantitative 2D 1H, 13C HSQC NMR Spectroscopy for the Determination of Chondroitin Sulfate and Dermatan Sulfate Content in Danaparoid Sodium - Gardini, Cristina; Boccardi, Giovanni; Guerrini, Marco; Kellenbach, Edwin; Lunenburg, Maarten; van der Meer, Jan-Ytzen; Naggi, Annamaria; Urso, Elena (Thrombosis and Haemostasis, 2023)
Objective Danaparoid sodium is a biopolymeric complex drug composed of the most abundant heparan sulfate (HS) followed in descending order by dermatan sulfate (DS) and chondroitin sulfate (CS). This composite nature explains its peculiar antithrombotic and anticoagulant properties and make it particularly advantageous when the risk of heparin-induced thrombocytopenia occurs. A specific control of the danaparoid composition is required by the Ph. Eur. The monograph includes the CS and DS limit contents and describes the method for their quantification through selective enzymatic degradations.Materials and Methods In this study, a quantitative two-dimensional nuclear magnetic resonance (NMR) method is proposed as a new method suitable for CS and DS quantification. Statistical comparison of the results provided by the analysis of a series of danaparoid samples with both NMR and enzymatic methods highlights a small systematic difference, likely derived from lyase-resistant sequences bearing oxidized terminals. Some modified structures, whose survival to the enzymatic action was confirmed by mass spectrometry, can be detected and quantified by NMR.Conclusion and Results The proposed NMR method can serve for the determination of DS and CS contents, is an easy-to-apply method with no dependence from enzymes and standards, and provides extensive structural information on the overall glycosaminoglycans mixture.
Keywords: danaparoid sodium; chondroitinases; NMR spectroscopy; glycosaminoglycans; LC-MS analysis